Urban Ruralities or the New Urban-Rural Paradigm - Introduction - Kress, Celina (International Planning History Society Proceedings, 2016)
Classical theories of urbanisation are based on a strict distinction of ‘the urban’ and ‘the non-urban’ and closely linked with concepts of order and organisation. Continuous statistics regarding the changing relation between people living in cities and outside cities and the extensive celebration of the demographic shift towards the ‘urban side’ in 2007 as a significant marker of the “Urban Age” clearly reflect this perspective. We do not question the general historic dichotomy of cities and the countryside but we oppose models which generally place the city in the centre or tend to colonise the country conceptually (“urbanised landscapes”, “planetary urbanism” etc.). The concept of “Urban Ruralities“ assembles research approaches which challenge a supposed hegemony of the 'urban order.' We propose to look at the city from its region and from the fringes. Shifting the perspective we want to find out about rural/non-urban logics and dynamics and their impact on urbanisation processes. Since the unfolding phase of town planning in the 19th century the formation and installation of order was a prerequisite for achieving healthy and just living conditions. Order became the equivalent of ‘the good city’ or ‘the urban.’ Accordingly the planning disciplines as well as the scholarly analysis of urbanising processes tend towards a conceptual prioritisation of order and ‘the urban’ over forms of disorder or non-urban and rural phenomena. In this session we rather propose to take into account a “complex relationality” of the opposing qualities: we are interested in examples which show and help explain that in most urbanising processes order and disorder, aspects of ‘the urban’ and ‘the rural’, are deeply entangled and belonging together as the two sides of a coin (new urban-rural paradigm). The four case studies of this session discuss two influential perspectives in this field: the planning and testing of modern infrastructure systems during the late 19th century in Berlin and Hanoi and the concept of 'Stadtlandschaft' in the reconstruction master plans of Madrid and Hamburg during the 1940s. Both topics are closely related and will display complementary manifestations of territorial, material, and representational ambivalence in urban-rural and centre-periphery relation. With this research we aim at a clearer conception of complex, uncontrolled and intertwined urban-rural assemblies and dynamics which dominantly materialise at the urban fringes, in zones of spatial, functional and habitual overlap, and in simultaneously growing and shrinking areas worldwide. We look for analytical tools to describe the continuously shifting condition of urban-rural relations and exchanges. This research can contribute to display, explain and conceptualise the resilience of cities through history – a focus of this conference.